Menerapkan Model Supervisi Akademik Berbasis Kolaborasi untuk Peningkatan Kualitas Pembelajaran di Madrasah - Ibnu Hibban; Susi Yusrianti (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Academic supervision plays a crucial role in improving the quality of learning in Islamic schools (madrasah), especially in ensuring that the learning process aligns with the principles and values of Islamic education. This research aims to critically examine the effectiveness of academic supervision in enhancing the quality of learning in madrasah based on a comprehensive literature review. Through a qualitative approach with a literature study design, this research explores and synthesizes various perspectives, findings, and concepts from relevant literature sources. The research results indicate that the effectiveness of academic supervision implementation in madrasah is influenced by several key factors, such as supervisor competence, teacher perceptions and participation, supervision methods used, support from the madrasah and stakeholders, as well as organizational environment and culture factors. To achieve optimal effectiveness, efforts are needed to develop structured supervision programs, supervisor training, and collaboration among stakeholders. Through effective academic supervision, it is expected that the quality of learning in madrasah can improve and better support the achievement of the goals of Islamic education. The research conclusions suggest the need for systematic supervision programs, enhancement of supervisor competencies, active teacher involvement, resource support, and collaboration among stakeholders in optimizing academic supervision in madrasah